Design of modified rhomboidal dualband antenna for Bluetooth and UWB applications - Singh A.; Pandey G.K.; Kalraiya S.; Singh H.S.; Meshram M.K. (My University, 2025)
A compact size, low profile microstrip fed dual band planer monopole antenna is presented. The shape of main radiating element is modified rhomboidal that covers ultrawideband (UWB) frequency range. Further, to make dual band antenna without affecting the UWB range, stair shaped strip in elliptical shaped slot is loaded on main radiating element. The dual band antenna covers 2.36 to 2.49 GHz (Bluetooth) and 3.1GHz to 17 GHz (UWB) frequency bands. The antenna is designed on FR4 substrate of size 35 × 24 × 1.6mm3. The parametric analysis, impedance bandwidth, input impedance, gain etc. of antenna are computed using Ansoft HFSS. © 2014 IEEE.